1998
DOI: 10.1046/j.1469-8137.1998.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐deficiency‐induced phytosiderophore release in in the calcicole grass Hordelymus europaeus

Abstract: Phytosiderophore (PS) release occurs under both iron and zinc deficiencies in representative Poaceae and has been speculated to be a general adaptive response to enhance the acquisition of micronutrient metals. We tested this hypothesis within an on-going study of the role of micronutrient metal nutrition for patterns of spontaneous vegetation in relation to soil pH and carbonate content. Hordelymus europaeus (L.) Harz, a negative grass species commonly found on soils rich in CaCO $ in Western Central E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…Uptake of the PS-Zn complex by maize (Zea mays L.) has been observed (von Wire n et al 1996). Gries et al (1998) observed Cu-de®ciency-induced PS release from the grass Hordelymus europaeus (L.) Harz. Increased exudation of PS by Zn-de®cient wheat (Triticum aestivum L. cv.…”
Section: Introductionmentioning
confidence: 97%
“…Uptake of the PS-Zn complex by maize (Zea mays L.) has been observed (von Wire n et al 1996). Gries et al (1998) observed Cu-de®ciency-induced PS release from the grass Hordelymus europaeus (L.) Harz. Increased exudation of PS by Zn-de®cient wheat (Triticum aestivum L. cv.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, the Strategy II mechanism involves the 1) synthesis of phytosiderophore (PS) in apical root zones (Romheld and Marschner 1986); 2) release of PS from the root apex (Marschner et al 1987); 3) solubilization of sparingly soluble Fe3+ by chelation with PS (Takagi et al 1984;Romheld and Marschner 1986); and 4) uptake of the PS-Fe3+ complex by roots (Takagi et al 1984;Marschner et al 1987). Furthermore, the release of PS has also been shown to be induced by Cu deficiency in calcicole grass (Gries et al 1998), Zn deficiency in wheat (Zhang et al 1991a), and Mn toxicity in barley (Alam et al 2000).…”
mentioning
confidence: 99%
“…Whether the limited availability of essential transition metals other than Fe, including Cu, Mn and Zn (Gries et al 1998), plays an Fig. 1 Total P concentrations of Cladonia furcata or C. rangiformis exposed for 1 h min to a deionized water or b KH 2 PO 4 (a=2 mM) at pH 3 or 8.…”
Section: Efficient Intracellular Fementioning
confidence: 99%
“…Calcifuge vascular plants are excluded from calcareous soils by their lacking ability to fulfill either their Fe or P requirements at high pH (Gries and Runge 1995;Tyler 1996;Zohlen and Tyler 2000). The availability of other transition metals, which are essential micronutrients (including Cu, Mn, Zn), can also be limiting (Gries et al 1998). Calcicole plants can, in turn, suffer from high concentrations of transition metals or Al at acidic sites (Tyler 1993).…”
Section: Introductionmentioning
confidence: 99%